Expressão dos receptores endometriais de estrógeno e progesterona em éguas acíclicas após administração de progesterona - Maciel, Luciana França Smith [UNESP] (2017)
Progesterone (P4) is frequently used after the administration of estradiol, to prepare seasonal non-cyclic mares as embryo recipients, however previous studies have reported gestation of seasonal non-cyclic mares treated only with P4. The objective of the present study was to evaluate the gene and protein expression of estrogen receptor alpha (ERα), estrogen beta (ERβ) and progesterone (PR) in the endometrium of seasonal non-cyclic mares treated with long acting progesterone (LAP4). Eight mares were used during the seasonal anoestrus phase, uterine biopsies were performed immediately before and five days after administration of 1,5 g of LA P4. Blood samples were taken daily for the determination of plasma P4 concentration. The protein expression of the receptors was evaluated by the immunohistochemistry and the immunostaining area percentage was determined by the ImageJ software. Transcripts abundance for ERα (ESR1), ERβ (ESR2) and PR (PGR) were determined by RT-qPCR. ERα showed higher protein expression (p <0.05) after administration of P4LA, but there was no change in mRNA abundance encoding this gene (p> 0,05). Tendency to lower protein expression was observed (p=0,07) and gene expression inhibition (p <0,05) for ERβ, PR did not changes (p>0,05). The plasma concentration of P4 presented a higher concentration 24 hours after the application of LA P4 (D1), with subsequent decline in these values (p<0,05). The 1.5 g dose of LA P4 reached the minimum concentrations of P4 required for the establishment and maintenance of gestation.